PRODUCTION OF HIGHLY EFFECTIVE SORBENTS BASED ON DOMESTIC RAW MATERIALS - Shoira Toirovna Adizova (Лучшие интеллектуальные исследования, 2024)
Annotation: The article discusses the views in the field of adhesion and autogenesis of high-molecular compounds on the development of polymer chemistry and adhesive substances produced by chemical industry enterprises and their importance in industrial development.